Settlement of Multiple Certificate Disputes On The Same Land Object - Rica Intan Febriyanti (Faculty of Law, Merdeka University Surabaya, 2021)
Land has an economic aspect with the value of the rupiah increasing every year, in the form of an increase in NJOP on SPPT PBB. Regarding legal land ownership through the inclusion of the owner's name on the land title certificate, several court decisions have found cases of double certificates which are original and authentic certificates. To determine who is entitled to the ownership of land rights in the same object, a lawsuit is made through the district court with the land office as a co-defendant. The purpose of this study is a legal remedy in the event of a land dispute due to dual certificates and the validity of the issuance of multiple certificates whose legality will be recognized according to law. This study uses empirical juridical methods, namely juridical research conducted by examining library materials called library research with a statute approach. Sources of Legal Materials used in this legal research use primary legal materials which are authoritative legal materials, meaning they have authority. The results of this study are the certificates issued by the land agency are valid until they are declared null and void by the district court, on the validity of the dual certificates, the applicable certificate is the land certificate which was issued earlier and declared valid by the panel of judges. Suggestions from this research are that the land office is expected to be more careful in conducting research on physical and juridical data in issuing land rights certificates.